Temperature characteristics at altitudes of 5–80 km with a self-calibrated Rayleigh–rotational Raman lidar: A summer case study. (February 2017) - Li, Yajuan; Lin, Xin; Yang, Yong; Xia, Yuan; Xiong, Jun; Song, Shalei; Liu, Linmei; Chen, Zhenwei; Cheng, Xuewu; Li, Faquan
Abstract: Temperature profiles at altitudes of 5–80 km are obtained with a self-calibrated Rayleigh–rotational Raman lidar over Wuhan, China (30.5°N, 114.5°E). By using the synchronous Rayleigh lidar temperature, rotational Raman temperature in the lower atmosphere could be calibrated and retrieved, which is free of other instruments (like local radiosondes). The results are comparable to the radiosonde calibration method. Based on the self-calibration approach, one-night (August 4–5, 2014) lidar temperature profiles are presented with radiosondes, NRLMSISE-00 model and TIMED/SABER data. Some interesting temperature characteristics have been present for studies of waves propagating from near ground level into the mesosphere. Temperature perturbations are found to increase exponentially with a scale height of ~10 km. The wavy structure shows minimal perturbations ('nodes') at some altitudes of 39, 52, 64 and 73 km. Dominant wavelengths and temperature variations are also analyzed at different time and altitudes. By comparison of the temperature and associate perturbations from the tropopause up to the stratopause, different amplitudes, phase fronts and vertical wavelengths are discovered as well. These discoveries indicate that some waves may originate in the lower atmosphere and propagate upward with decreasing static stability. Highlights: A combined Rayleigh and rotational Raman lidar covers a large detection range from the troposphere up to the mesosphere (5–80 km). RR temperatures are retrieved by a self-calibration method using synchronous Rayleigh lidar temperature instead of other instruments. Temperature characteristics are analyzed for studies of waves propagating from almost ground level into the lower thermosphere.